Phytosociological studies of weeds associated with rice in Ri-Bhoi district of Meghalaya - John, Chris; Ram, Vishram; Panda, Sushree; Pusparani, Ngangbam (ORYZA-An International Journal of Rice, 2023)
Rice-based cropping systems are predominant in Meghalaya, India, comprising rice-potato, rice-mustard, rice-pea and rice monocropping systems. In areas that have shifted to cultivating cash crops, rice has supplanted the consumption of millet and maize as the principal staple. Thus, paddy-based weed assemblages are of significant importance in maximizing grain yields. Characterization and descriptive analysis of weed communities in crops can be brought about by phytosociological studies. Knowledge of the relative importance of spatial and temporal variables, environmental conditions and management practices as filters for weed assemblages will prove to be useful in putting together an effective decision support system for their management. Through this comparative survey of 66 paddy fields, distributed homogenously throughout Jirang, Umling and Umsning blocks of Ri-Bhoi, an attempt has been made to study the weed vegetation associated with paddy in the Ri-Bhoi district of Meghalaya, in order to assess the effects of agricultural intensification on the diversity, structure and composition of weed communities. Jirang block recorded the maximum weed diversity, followed by Umsning and Umling blocks. Understanding the connections between weed species and landscape elements is necessary for developing alternative weed management strategies.